Oral manifestations of Nance Horan syndrome: A systematic review of case reports - Ankita Mathur; Sapna Negi; Snehasish Tripathy; Shalini Aggarwal; Felix Amekpor; Vini Mehta (Oral Oncology Reports)
Nance Horan Syndrome (NHS) is a rare congenital genetic condition. However, due to the sporadicity of cases and the similarity in manifestations of mild NHS with X-linked cataracts, it is difficult for clinicians and researchers to diagnose and treat NHS. Therefore, we undertake a comprehensive review of the existing literature on the oral manifestations of NHS and, its definitive diagnosis based on oral and craniofacial symptoms. An electronic search of PubMed-MEDLINE, Embase, Scopus, and Google Scholar databases was done to retrieve case reports documenting oral anomalies related to NHS at the time of presentation. Genetic studies or studies focussing on the genetic analysis of the case were excluded. Descriptive statistics were used to calculate simple frequency, percentages, and proportions to identify trends and commonalities in presenting symptoms and oral assessment findings. Out of 2086 identified studies, 12 studies that met the inclusion criteria were reviewed. Most patients' ages ranged from between 4 and 12 years of age. Out of 31 affected individuals, 11 were females and 20 were males. Screwdriver-shaped incisors (75 %) often accompanied by the presence of supernumerary teeth and diastema (66 % studies), Hutchinson incisors (50 % studies), Mulberry molar (41.6 %) malocclusion (58.3 % studies) were commonly seen. Besides that, talon cusps, agenesis/non-eruption of teeth, premolars, and Taurodontism were also observed. Facial dysmorphism was common in all the studies. An in-depth understanding of these anomalies will enable dental practitioners to provide specialised care, including focused interventions and preventive measures to address the oral health issues associated with NHS.